To simplify \((\sqrt{3} + 2)^2\), we can expand it using the formula for the square of a binomial:
\[ (a + b)^2 = a^2 + 2ab + b^2 \]
Here, \(a = \sqrt{3}\) and \(b = 2\).
Now we calculate each part:
- \(a^2 = (\sqrt{3})^2 = 3\)
- \(b^2 = 2^2 = 4\)
- \(2ab = 2(\sqrt{3})(2) = 4\sqrt{3}\)
Putting this all together:
\[ (\sqrt{3} + 2)^2 = a^2 + 2ab + b^2 = 3 + 4\sqrt{3} + 4 \]
Now, combine the constant terms:
\[ 3 + 4 = 7 \]
So, we have:
\[ (\sqrt{3} + 2)^2 = 7 + 4\sqrt{3} \]
Thus, the simplified form is \(7 + 4\sqrt{3}\).
The correct answer is:
D. \(7 + 4\sqrt{3}\)